A study to assess the knowledge regarding blood donation among general population attending primary health centre of Dhawa, Jodhpur, Rajasthan - Pandey, Vandna; Kurien, Nancy; Kumari, Krishna; Garg, Lata; Yadav, Manisha; Choudhary, Mahima; Rani, Mamta; Kashyap, Mansi (International Journal Of Community Medicine And Public Health, 2021)
Background: Human blood is an essential element of the human life and there is no substitute for it. Blood donation save lives during critical situation but several thousands of patients who need blood transfusion do not receive timely access to safe blood. Today, blood transfusion services constitute a crucial part of any health care delivery system. Adequate and safe supply of blood and blood component is essential. Methods: Present study has been carried out among general population of community attending primary health center. Quantitative research approach was used to assess the knowledge regarding blood donation. Data was collected through self-structured knowledge questionnaire. Sixty samples were selected by non-probability convenient sampling technique. Results: In the study there were 60 subjects, in which male were 33(55%) and female were 27(45%). Ten subjects had excellent knowledge, 21 subjects had good knowledge, 20 subjects had average knowledge and 9 subjects had poor knowledge. Statistically significant association was found between knowledge score and selected demographic variables (i.e., gender and occupation) at p<0.05 level of significance. Conclusions: The study indicates that awareness session on blood donation should be held regularly to improve the knowledge and create positive attitude and remove the misconception among general population about blood donation.